Nanoparticles as a potential protective agent for arsenic toxicity alleviation in plants. (1st May 2022) - Kandhol, Nidhi; Aggarwal, Bharti; Bansal, Ruchi; Parveen, Nishat; Singh, Vijay Pratap; Chauhan, Devendra Kumar; Sonah, Humira; Sahi, Shivendra; Grillo, Renato; Peralta-Videa, José; Deshmukh, Rupesh; Tripathi, Durgesh Kumar
Abstract: Aggrandized technological and industrial progression in past decades have occasioned immense depreciation in the quality of environment and ecosystem, majorly due to augmentation in the number of obnoxious pollutants incessantly being released in soil, water or air. Arsenic (As) is one such hazardous metalloid contaminating the environment which has the potential to detrimentally affect the life on earth. Even in minute quantity, As is known to cause various critical diseases in humans and toxicity in plants. Recent studies on nanoparticles (NPs) approve of their ability to qualify the criterion of becoming a potent tool for mitigating As-induced phytotoxicity. Nanoparticles are reported to promote plant growth under As-stress by stimulating various alterations at physiological, biochemical, and molecular levels. In this review, we provide an up-to-date compilation of research that has been carried out in comprehending the mechanisms utilized by nanoparticles including controlled As uptake and distribution in plants, maintenance of ROS homeostasis during stress and chelation and vacuolar sequestration of As so as to reduce the severity of toxicity induced by As, and potential areas of research in this field will also be indicated for future perspectives. Highlights: NPs restricts AsIII uptake through down regulation of Lsi1 and Lsi1 transporters. NPs maintain root and shoot biomass, photosynthesis, and nutrient uptake. Antioxidant production is boosted by NPs to maintain ROS under As stress. NPs increase GSH and PCs to promote vacuolar sequestration of As.